A rare life‐threatening complication of acute mastoiditis: Case report and literature review. Issue 7 (9th July 2021) - Oommen, Jerry Z.; Valiuddin, Hisham; Ring, Hope; Shotkin, Paul
Abstract: Severe complications may not always present with "classic" signs and symptoms. In the setting of recent mastoiditis, complications including cerebral venous sinus thrombosis, skull base osteomyelitis, and retropharyngeal abscess should be considered, particularly with persistent or worsening symptoms. A broad differential can lead to prompt diagnosis and treatment, thereby reducing the likelihood of morbidity and mortality. Abstract : Severe complications may not always present with "classic" signs and symptoms. In the setting of recent mastoiditis, complications including cerebral venous sinus thrombosis, skull base osteomyelitis, and retropharyngeal abscess should be considered, particularly with persistent or worsening symptoms. A broad differential can lead to prompt diagnosis and treatment, thereby reducing the likelihood of morbidity and mortality.